MOHAMMAD IN ARCHIPELAGO: SPATIALIZING SPIRITUALITY IN MAJELIS SHALAWAT SYUBBANUL MUSLIMIN IN KALIKAJAR PROBOLINGGO - Nurul Huda (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2017)
Using Mohammad in Archipelago as a metaphor of the postmodern religious landscape, this article argues that Mohammad, a prophet of Muslim born in Mecca Saudi Arabia, has undoubtedly become a consumer item in shalawat council (Majelis Shalawat) practiced in many areas of Indonesia, including Probolinggo. This new religious phenomenon has been reproduced in line with the emergence of blurred negotiation between the profane and the sacred, and by the fact that religion is always posed in social life and in business life, shalawat practice also depends itself on the meaning and process making, or the certain socio-cultural context. This study sets the Majelis Shalawat Syubbanul Muslimin, located at Probolinggo, in relation with the ways they reproduced its penetration of religion vis-a-vis market economy. It also portrays how Syubbanul Muslimin produced a spatial order of certain followers since they have successfully practiced modes and techniques of production, consumption, and structuration of their own spiritual market. Additionally, it also contributes to the construction of charisma they have shaped by using the economicpolitical discourse of media.